Immunomodulatory effects of mononuclear 5,6-epoxy-5,6-dihydro-1,10-phenanthroline platinum(II) complex - Stanisavljević Isidora; Živković Marija; Rajković Snežana; Obradović Milica; Jurišević Milena; Pavlović Slađana; Simović-Marković Bojana; Gajović Nevena; Ćorović Irfan; Jocić Miodrag; Kostić Andrija; Jovanović Ivan (Kragujevac Journal of Science)
The newly developed mononuclear 5,6-epoxy-5,6-dihydro-1,10phenanthroline platinum(II) complex revealed notable antitumor effects in vitro and in vivo. In this study, the effects of this platinum(II) complex on the immune response were assessed. Peritoneal macrophages and splenocytes obtained from mice were treated with lipopolysaccharide (LPS)/Concanavalin A (ConA) along with platinum(II) complex and measurement of cytokine concentrations and immunophenotyping was performed. Our findings indicate that the platinum(II) complex exhibits significant immunomodulatory effects on peritoneal macrophages and splenocytes.